COVID-19 and Immigrants’ Increased Exclusion: The Politics of Immigrant Integration in Chile and Peru - Freier, Luisa Feline; Vera Espinoza, Marcia (Frontiers in Human Dynamics, 2021)
The COVID-19 sanitary crisis has put into sharp relief the need for socio-economic integration of migrants, regardless of their migratory condition. In South America, more than five million Venezuelan citizens have been forced to migrate across the region in the past five years. Alongside other intra-regional migrants and refugees, many find themselves in precarious legal and socio-economic conditions, as the surge in numbers has led to xenophobic backlashes in some of the main receiving countries, including Chile and Peru. In this Perspective, we will explore in how far the COVID-19 crisis has offered stakeholders an opportunity to politically reframe migration and facilitate immigrant integration or, rather, further propelled xenophobic sentiments and the socio-economic and legal exclusion of immigrants.